Left Ventricular Lead Electrical Delay Is a Predictor of Mortality in Patients With Cardiac Resynchronization Therapy. (October 2015) - Roubicek, Tomas; Wichterle, Dan; Kucera, Pavel; Nedbal, Pavel; Kupec, Jindrich; Sedlakova, Jana; Cerny, Jan; Stros, Jan; Kautzner, Josef; Polasek, Rostislav
Abstract : Background—: Electric left ventricular lead position, assessed by the electric delay from the beginning of the QRS complex to the local LV electrogram (QLV), was found in previous studies to be a strong predictor of short-term response to cardiac resynchronization therapy. We hypothesized that suboptimum electric position of the left ventricular lead is associated with an excess of heart failure events and mortality. Methods and Results—: We analyzed the clinical outcome of patients with left bundle branch block or intraventricular conduction delay treated with cardiac resynchronization therapy at our institution during 9 years. Baseline clinical characteristics, QLV/QRS duration (QLV ratio) at cardiac resynchronization therapy implant, and data about heart failure hospitalization and mode of death were collected in 329 patients who were followed for a period of 3.3±1.9 years. Of them, 83 were hospitalized for heart failure and 83 died. Event rates for all-cause mortality, cardiac mortality, noncardiac mortality, heart failure mortality, and sudden death were 25.2%, 14.9%, 10.3%, 12.2%, and 2.1%, respectively. Patients with a QLV ratio ⩽0.70 had significantly worse event-free survival for all study end points—hazard ratio, 1.6; 95% confidence interval, 1.0 to 2.4; P =0.05 for heart failure hospitalization; hazard ratio, 2.9; 95% confidence interval, 1.6 to 5.5; P =0.001 for heart failure mortality; hazard ratio, 1.8; 95% confidence interval, 1.1 to 2.7; P =0.01 for cardiac mortality; and hazard ratio, 2.1; 95% confidence interval, 1.2 to 3.7; P =0.01 for all-cause mortality. In multivariable analysis, QLV ratio ⩽0.70 remained associated with all study end points. Conclusions—: Electric left ventricular lead position in cardiac resynchronization therapy patients was a significant predictor of heart failure hospitalization and mortality.